MAHAD AL-JAMIAH DAN KESALEHAN SOSIAL, STUDI KASUS MAHAD AL-JAMIAH IAIN BUKITTINGGI - Yusuf Afandi (Islam Transformatif : Journal of Islamic Studies, 2019)
This Study discusses Mahad al-Jamiah IAIN Bukittinggi and the social piety of the students in Mahad al-Jamiah IAIN Bukittinggi. The object of study is the programs implementted by Mahad al-Jamiah IAIN Bukittinggi. This study was analyzed using the theory of social piety that was initiated by Wasisto Raharjo about the concept Ideal of social piety. The results of this study are the implications of the Mahad al-Jamiah IAIN Bukittinggi program for social piety is the practice of religion and habituation of worship, the moderation of understanding Mahasantri religion as well as the religious and social piety of Mahasantri Mahad al-Jamiah IAIN Bukittinggi.